2016
DOI: 10.1007/s00464-016-5376-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of super–super obese patients: comparison between one anastomosis (mini) gastric bypass and Roux-en-Y gastric bypass

Abstract: One anastomosis (mini) gastric bypass yields superior weight loss at 18 and 24 months in comparison with Roux-en-Y gastric bypass in patients with BMI of ≥60 kg/m. Findings need confirmation in larger randomized studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The higher weight loss amongst the MGB group compared to RYGB group is in keeping with previously published studies including from our group . The reported incidence of anaemia after MGB varies from 5.0% to 27.0% .…”
Section: Discussionsupporting
confidence: 91%
“…The higher weight loss amongst the MGB group compared to RYGB group is in keeping with previously published studies including from our group . The reported incidence of anaemia after MGB varies from 5.0% to 27.0% .…”
Section: Discussionsupporting
confidence: 91%
“…Alimentary limb elongation, cruroplasty, Hill-type gastropexy, or partial fundoplication using the gastric remnant or even a Belsey-Mark IV procedure are possible solutions [19]. Endoscopic procedures and techniques (Stretta®, LINX®) may become valuable in the near future, as new devices are now available with interesting outcomes [20,21,29].…”
Section: Discussionmentioning
confidence: 99%
“…The mini‐gastric bypass, or more recently termed single‐ or one‐anastomosis gastric bypass (OAGB), is a simple alternative to RYGB performed with one anastomosis but results in more acid and bile reflux . In patients with very high BMI (≥ 60 kg/m 2 ), Parmar et al found that OAGB achieved greater weight loss at 18 and 24 months compared with RYGB. Moreover, in patients with milder BMI elevations, OAGB with a longer (80 cm) biliopancreatic limb had better T2D remission rates than RYGB .…”
Section: Executive Summarymentioning
confidence: 99%